2023
DOI: 10.22541/au.169735631.12270370/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ST analysis plus CTG compared to CTG alone for intrapartum fetal monitoring (the START randomised controlled trial): A cost minimisation study.

Chris Wilkinson,
Camille Schubert,
Bronni Simpson
et al.

Abstract: Objective: To undertake a cost minimisation study of ST analysis (STan) plus cardiotocograpy (CTG) compared to CTG alone. Design: Cost-minimisation analysis alongside a randomised controlled trial [(1)](#ref-0001). Setting: A tertiary level maternity centre in Adelaide, South Australia. Population: Women in labour ≥36 weeks gestation, with a clinical indication for continuous electronic fetal monitoring. Methods: We utlilised a health service perspective covering randomisation to final maternal and neonatal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…With the actual number randomized, the statistical power to detect the original difference of 5% was only approximately 56%. At the time of performing power and sample size calculations for the trial 20 , the rate of EmCS at the trial institution was approximately 18% (WCH Clinical Information Service (CIS) data, 2015); this proportion was revised down to 17% for the power calculation, due to introduction of a rigorous fetal surveillance education program mandated by the health department for all obstetric and midwifery staff involved in intrapartum care. We considered that this program itself would decrease the WCH EmCS rate, regardless of the addition of STan as an adjunct to CTG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the actual number randomized, the statistical power to detect the original difference of 5% was only approximately 56%. At the time of performing power and sample size calculations for the trial 20 , the rate of EmCS at the trial institution was approximately 18% (WCH Clinical Information Service (CIS) data, 2015); this proportion was revised down to 17% for the power calculation, due to introduction of a rigorous fetal surveillance education program mandated by the health department for all obstetric and midwifery staff involved in intrapartum care. We considered that this program itself would decrease the WCH EmCS rate, regardless of the addition of STan as an adjunct to CTG.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sample size was based on data from our pilot study 20 , FBS reduction rates and the observed rate of EmCS at the WCH. The proportion of EmCS deliveries in the CTG only (control) group was expected to be approximately 17%, and the sample size was intended to provide 80% power (with two-sided α = 0.05) to detect a 5% absolute reduction in the rate of EmCS in the CTG + STan group (i.e.…”
Section: Sample Size Calculationmentioning
confidence: 99%